Analyses of house-owners’ awareness and compliance with urban greenery regulations in Madina, Ghana - Seth Akagla; Yaw Agyeman Boafo (Discover Environment)
Abstract The transformation of natural landscapes due to ongoing urbanization highlights the critical need for the presence and integration of vegetation within urban environments. Although the benefits of urban greenery, including biodiversity conservation, pollution mitigation, and reduction of urban heat island effects, are widely recognized, adherence to corresponding building regulations poses a significant challenge in many Global South countries, including Ghana. This study investigated the compliance with urban greenery regulations among house owners in Madina, a rapidly urbanizing suburb of Accra, Ghana. The research utilized a mixed-methods approach, combining quantitative surveys with house-owners (n = 200) with qualitative interviews (n = 8) to explore the levels of awareness and compliance among residential house-owners with the guidelines stipulated in the Ghana Building Regulations (LI 1630) and the Ghana Building Code 2018. Our findings revealed a significant gap between awareness of the benefits of urban greenery and actual compliance with the regulations designed to ensure its provision. Key factors contributing to non-compliance were socioeconomic pressures, such as the high cost of land and accommodation, and institutional barriers, including bureaucracy, weak enforcement, and insufficient resources. Furthermore, administrative and political challenges, such as corruption and a lack of support, exacerbate the situation. The study recommends targeted actions to enhance compliance rates, emphasizing the need for streamlined regulatory processes, more robust enforcement mechanisms, and increased awareness campaigns to highlight the critical importance of urban green spaces.